Effectiveness of Social Media on Purchase Intention: Women Led SMEs In Northern Province Of Sri Lanka - Kumaradeepan, V. (University of Jaffna, 2022)
The social media is having the direct influence towers the consumers purchasing intention. This purchasing intention having influenced on buying attitude of the customers especially the small and medium enterprises in noticeably different from others because of their marketing campaign. The aim of the Research paper was to explore the impact of social media effectiveness on consumer purchase intention among women led small and medium enterprises (SMEs) in Northern part of Sri Lanka including Jaffna, Killinochchi, Mullaithivu, Mannar and Vavuniya. Social media effectiveness (trust, Customization, interaction, word of mouth, trend, entertainment and customer engagement) as independent variable and purchase intention as dependent variable. This is deductive approach of quantitative method. Primary data were collected through self-administrated closed ended questionnaires from women led SMEs in Northern Province of Sri Lanka. 400 questionnaires issued to women led SMEs in Northern Province of Sri Lanka and received only 310 filled questionnaires in return. Data were analysis with the help of SPSS (22) statistical tool. Findings of the research conclude that that trust, customization, Interaction, e-Word of mouth, trendiness, entertainment, and customer engagement as important factors impact on purchase intention. Mostly entertainment and customer engagement shows higher correlation on consumer purchase intention. Further studies could be cover entire Sri Lanka as target population.
Keywords: Social Media effectiveness; Purchase Intention; Women led SMEs